2022
DOI: 10.3389/fmicb.2022.1015588
|View full text |Cite
|
Sign up to set email alerts
|

The responses to long-term nitrogen addition of soil bacterial, fungal, and archaeal communities in a desert ecosystem

Abstract: Nitrogen (N) deposition is a worldwide issue caused by human activity. Long-term deposition of N strongly influences plant productivity and community composition. However, it is still unclear how the microbial community responds to long-term N addition in a desert ecosystem. Therefore, a long-term experiment was conducted in the Gurbantonggut Desert in northwestern China in 2015. Four N addition rates, 0 (CK), 5 (N1), 20 (N2), and 80 (N3) kg N ha−1 yr.−1, were tested and the soil was sampled after 6 years of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The impact of atmospheric nitrogen (N) deposition on soil carbon (C) and nitrogen (N) cycling in temperate deserts remains a subject that requires further understanding due to the complex responses of soil microbial communities to increasing N levels [1][2][3][4]. Previous studies have shown the nonlinear responses of soil microbial communities to various N addition doses, indicating the potential variations in their response, which is dependent on the experimental region and N dose [5][6][7][8][9][10][11]. Furthermore, variations in the soil N background and microorganisms among studies, as well as the potential for N saturation, can influence microbial responses.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of atmospheric nitrogen (N) deposition on soil carbon (C) and nitrogen (N) cycling in temperate deserts remains a subject that requires further understanding due to the complex responses of soil microbial communities to increasing N levels [1][2][3][4]. Previous studies have shown the nonlinear responses of soil microbial communities to various N addition doses, indicating the potential variations in their response, which is dependent on the experimental region and N dose [5][6][7][8][9][10][11]. Furthermore, variations in the soil N background and microorganisms among studies, as well as the potential for N saturation, can influence microbial responses.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous increase in nitrogen (N) deposition resulting from various human activities, such as industry, agriculture, and livestock farming, has emerged as a significant driver of global environmental change, impacting both forest and soil ecosystems ( Peng et al, 2017 ; He et al, 2023 ; Huang et al, 2023 ). Within the soil ecosystem, N input affects the soil physicochemical property, enzyme activity and the relative abundance of gene expression ( Cardinale et al, 2020 ; Chen et al, 2021 ; Liu et al, 2022 ; Zhang X. et al, 2022 ). Previous studies have demonstrated that N addition significantly raised total nitrogen (TN) and available nitrogen (AN) levels, while reducing pH due to increase hydrogen proton concentration, resulting in soil acidification and promoting soil organic carbon (SOC) degradation in the rhizosphere soil of wheat fields and Cunninghamia lanceolate forests ( Liu et al, 2022 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…N input not only regulates soil physicochemical property and enzyme activity, but also exerts a profound influence on the proliferation, diversity, community composition, relative abundance and metabolic function of soil microorganisms ( Ma et al, 2021 ; Si et al, 2022 ; Zhang X. et al, 2022 ). N addition has been reported to reduce the soil bacterial diversity, with significant correlation with physicochemical properties, and it also leads to increase relative abundances of Proteobacteria and Actinobacteria ( Dai et al, 2018 ; Zhang X. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations